Positive correlation of fitness with group size in two biotypes of Russian wheat aphid (Homoptera: Aphididae) - Michaud, J. P.; Jyoti, J. L.; Qureshi, Jawwad A. (My University, 2011)
Changes in Þtness parameters as a function of colony size (one versus 10 aphids) were measured in two biotypes (RWA1 and RWA2) of the Russian wheat aphid, Diuraphis noxia (Mordvilko) (Homoptera: Aphididae), feeding on three cultivars of wheat, Triticum aestivum L., at two temperatures. ÔTregoÕ is a cultivar with no speciÞc resistance to D. noxia, whereas, ÔStantonÕ and ÔHaltÕ express Dny and Dn4 resistance sources, respectively. Feeding in a group accelerated the development of RWA1 on Trego and Stanton at 20 C, but not at 24 C, whereas grouped RWA2 developed faster than solitaryRWA2on all three cultivars at 24 C, but not at 20 C. Survival (Þrst instarÐadult) ofRWA2 also was improved by grouping on Stanton and Halt at 24 C, but solitaryRWA2survived better at 20 C on all three cultivars. The reproductive rate ofRWA1was improved by grouping on Trego and Stanton at both temperatures, but only on Halt at 24 C. Lifetime fecundity of RWA1 also was increased by grouping in all cases except for Trego at 20 C. Grouped development increased the reproductive rate of RWA2 on all three cultivars at 24 C, but had no effect at 20 C. Grouped RWA2 developed and reproduced faster than grouped RWA1 on all three cultivars at 24 C. Thus, the Þtness of D. noxia was positively correlated with group size during colony establishment, but the effects were sensitive to temperature, being more pronounced at 20 C for RWA1 and at 24 C for RWA2.
Keywords: Development; Diuraphis noxia; Reproduction; Survival; Temperature